(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article discusses professional responsibility in public relations activities in the development of communication strategies that involve the relationship with influencers. Shares part of the results of empirical research Grounded Theory (PARAVENTI, 2020) on ethics in public relations and confronts them with the guidelines of the Conar Guide to Advertising by Influencers (CONAR, 2021). There is a demand to expand the professional and academic discussion about the effects of sponsored and conflicting influence on the public sphere.